Os efeitos e a aplicação do parágrafo único do Artigo 444 da CLT nas relações individuais de trabalho - Xavier, Saulo Rodrigues (2019)
The Brazilian Federal Statute no. 13,467/2017, known as the Labor Reform, has created a new provision in the sole paragraph of article 444 of the Consolidation of Labor Laws (CLT). The text of said new provision authorizes individual negotiation between employee and employer and sets forth the prevalence of the individual negotiation over collective-bargaining agreements, stating that both documents have the same effectiveness. The new legal provision authorizes individual negotiation exclusively when it involves workers who hold an undergraduate degree and whose wage is as much as or over twice the amount of the Social Security ceiling. The provision also limits individual negotiation to the matters established in article 611-A of CLT. The mentioned Labor Reform innovation requires a comprehensive analysis of both its application and effectiveness. In this context, examining the legal content of the employment relationship and whether such individual negotiation violates the principles of equality, isonomy, and protection – which are so precious to Labor Law – is absolutely vital. Another essential element in the analysis of this negotiation is undoubtedly the autonomy of the employee's will. Finally, a brief examination of the matters subject to negotiation – as authorized by the statute itself – is necessary. This research has the objective of investigating the application and effects of this novelty introduced into CLT